2002
DOI: 10.1046/j.1472-4642.2002.00155.x
|View full text |Cite
|
Sign up to set email alerts
|

Place prioritization for biodiversity reserve network design: a comparison of the SITES and ResNet software packages for coverage and efficiency

Abstract: The place prioritization problem in conservation biology is that of establishing a sequentially prioritized list of places on the basis of biodiversity content. Such a list can then be used to select reserve networks that are designed to be fully representative of the biodiversity of an area as efficiently as possible (for instance, with minimum area or cost). The usual goal is the representation of all chosen biodiversity surrogates up to or beyond a required target, or to the greatest available extent. The p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
33
0
3

Year Published

2005
2005
2014
2014

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(39 citation statements)
references
References 9 publications
3
33
0
3
Order By: Relevance
“…The absolute agreement between the totally different approaches demonstrates the solidness of the final solution. These results also confirm the advantage of the combined use of different software packages, as Kelly et al (2002) reported.…”
supporting
confidence: 89%
See 2 more Smart Citations
“…The absolute agreement between the totally different approaches demonstrates the solidness of the final solution. These results also confirm the advantage of the combined use of different software packages, as Kelly et al (2002) reported.…”
supporting
confidence: 89%
“…Just as Kelly et al (2002) assessed and recommended the combined use of different software, our combined use of programmes based on different philosophies (heuristic and meta-heuristic ones) was demonstrated as a powerful tool.…”
Section: B Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…It would be difficult to choose among them, although a few guidelines for doing so could be established. The shorter solution, obtained by simulated annealing (8 quadrats), is problematic since it omits three species, one of them endemic to the biome, thus supporting Kelley et al (2002) who recently found that heuristic, sequential algorithms in some instances may be advantageous in relation to optimized global solutions. In addition, sequential solutions may be preferable for practical applications since they result in a priority rank that is possibly useful in dealing with hotspots (such as cerrado) or with organisms, such as anurans, that are very sensitive to environmental changes.…”
Section: Discussionmentioning
confidence: 79%
“…In the three methods used, the purpose is to keep all species represented at least once in the network (the target). Following Kelley et al (2002), the three solutions were compared using Jaccard coefficients.…”
Section: Methodsmentioning
confidence: 99%